THE ADVANTAGE OF ORGANIZING THE TRAINING PROCESS FOR PHYSICAL EDUCATION TEACHERS USING INFORMATION AND COMMUNICATION TECHNOLOGIES - Eryigitov Dilshod Kholboyevich (Journal Park Publishing, 2023)
This article discusses the advantages of future physical education teachers in organizing the educational process on the basis of information and communication technologies.
Keywords: information process, professional and pedagogical skills, social requirements, pedagogical skills, modern information technologies, information creation.